Changes in the system of anthroponyms in the Uzbek language at the end of the 20th century - the beginning of the 21st century - Koziyeva Iqbal Komiljonovna (Zien Journals, 2022)
This article covers the issues related to the anthroponymics branch of the field of onomastics. The concept of anthroponym, its scope, types of anthroponym, name and its meaning are described in detail. The article focuses on the uniqueness of the Uzbek people in choosing a name, national traditions and values.
Keywords: onomastics; anthroponym; name; surname